Sexual Grooming of Children Mode through Live Streaming: Legal Gaps in the Face of Anonymity of Online Transactions - L. Alfies Sihombing; Yeni Nuraeni; Wahyudi Wahyudi; Loso Judijanto; Abidah Abdul Ghafar (Universitas Negeri Semarang, 2025)
The rapid development of digital technology has enabled new forms of child sexual exploitation, including sexual grooming conducted through live-streaming platforms. This phenomenon demonstrates not only the heightened vulnerability of children in cyberspace but also the limitations of national legal frameworks in addressing crime patterns characterized by anonymity and online financial transactions. This study employs a combined normative and empirical juridical approach to provide a comprehensive understanding of online grooming cases in Indonesia. The normative component analyzes statutory provisions, child protection laws, and digital platform regulations to identify the intended legal protections for children. The empirical component complements this by collecting first-hand insights through semi-structured interviews with law enforcement officers, representatives of the Indonesian Child Protection Commission (KPAI), digital platform operators, and victim support companions. The integration of these approaches reveals gaps between legal norms and enforcement practices, particularly regarding institutional constraints, reporting mechanisms, and socio-technical challenges faced in case handling. The findings show that grooming through live streaming involves complex psychological manipulation facilitated by platform features that allow perpetrators to maintain anonymity. Current regulations do not explicitly recognize online grooming as a distinct criminal offense, nor do they adequately address anonymous electronic transactions commonly used in this crime. Court decisions also illustrate inconsistencies in legal application due to the absence of specific norms governing technology-based grooming. These findings highlight the urgency of reformulating national legal policies by introducing explicit criminal norms on digital grooming, strengthening penalties for online media–based sexual crimes, and regulating anonymous online transactions. The study further recommends enhancing the role of digital financial institutions and technology platforms in prevention, monitoring, and reporting mechanisms. In addition, community-based education and preventive interventions are essential to complement law enforcement efforts and create a safer digital environment for children.